The Effect of STAD Learning Model on Learning Motivation of Elementary School Students - Dede Iman Suhendra; Agi Ginanjar; Mochamad Zakky Mubarok; Reyan Novaldi (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to examine the difference between the effect of the STAD learning model and the effect of the conventional learning model on elementary school student learning motivation. The research used an experimental method with a non-equivalent control group design. The participants were 26 sixth graders in one of the elementary schools in Indramayu district taken using systematic sampling. The research instrument used a learning motivation questionnaire in physical education for elementary school students. The analysis technique used an independent-samples t-test. The results of the study concluded that there was a difference between the effect of the STAD learning model and the effect of the conventional learning model on the learning motivation of elementary school students. Further investigation of the use of the STAD learning model on other affective aspects, especially creativity, is needed. In addition, it is suggested to conduct research with larger number of participants so that the results of this study can be generalized, especially at the elementary school level.